Intracardiac Foreign Body (Bone Cement) after Percutaneous Vertebroplasty - Yang, Jun Ho (Korean Society for Thoracic and Cardiovascular Surgery, 2013)
Percutaneous vertebroplasty is a relatively easy and minimally invasive procedure used in treating vertebral fractures. However, the procedure has many complications, one of which is bone cement leakage, which happens frequently. Leakage to the paravertebral venous system, in particular, may lead to especially devastating consequences. Here we report a case of a 65-year-old male patient with an intracardiac foreign body (bone cement) that generated a perforation on the right ventricle, and result in hemopericardium after percutaneous vertebroplasty. We performed open heart surgery to remove the foreign body.